Goodnight mommy [videorecording (DVD)] - Fiala, Severin, 1985-; Wuest, Susanne; Schwarz, Lukas; Schwarz, Elias (Anchor Bay Entertainment, 2015)
In this atmospheric, nerve-straining chiller, two young twins confined to an isolated country house transform their resentment towards their mother into a fatal illusion about her identity. In the heat of the summer, a lonesome house in the countryside between woods and corn fields. Nine-year-old twin brothers are waiting for their mother. When she comes home, bandaged after cosmetic surgery, nothing is like before. The children start to doubt that this woman is actually their mother.